Gangguan Aspek Morfologis dan Sintaksis pada Penderita Disleksia Usia 13 Tahun - Nada Hanifah; Ismah Rahayu; Dona Aji Karunia Putra (Universitas Mulawarman, 2023)
This study aims to describe the form of language disorders in morphological and syntactic aspects in dyslexic patients aged 13 years. This research is qualitative descriptive research. The subject of this research is a 13-year-old dyslexic with the initials SR, a junior high school student. Data collection techniques with test techniques with written tests to the subject, including a random sentence compilation test and a picture-telling test. The first test amounted to 10 items whose sentence content adjusted Indonesian language learning at the subject's school level. The results of this study show that two aspects of language are disrupted in dyslexic children, namely morphological and syntactic aspects. Morphological aspects include letter addition, letter removal, letter writing errors, letter replacement, letter placement in reverse, removal-replacement, and removal-addition. One of the effects of dyslexia on morphological ability is that SR cannot write words well. On the other hand, syntactic aspect errors include function structure in compound sentences, imperative sentence structure errors, structure errors in procedure sentences, and omission of predicates. From the errors made by SR, it can be proven that SR tends to reverse the sentence structure due to the difficulty in stringing words together.